The Role of miR-126 in Critical Limb Ischemia Treatment Using Adipose-Derived Stem Cell Therapeutic Factor Concentrate and Extracellular Matrix Microparticles - Procházka, Václav; Jurčíková, Jana; Vítková, Kateřina; Pavliska, Lubomír; Porubová, Ludmila; Lassák, Ondrej; Buszman, Piotr; Fernandez, Carlos A; Jalůvka, František; Špačková, Iveta; Lochman, Ivo; Procházka, Martin; et al. (Medical science monitor, 2018)
BACKGROUND Paracrine factors secreted by adipose-derived stem cells can be captured, fractionated, and concentrated to produce therapeutic factor concentrate (TFC). The present study examined whether TFC effects could be enhanced by combining TFC with a biological matrix to provide sustained release of factors in the target region. MATERIAL AND METHODS Unilateral hind limb ischemia was induced in rabbits. Ischemic limbs were injected with either placebo control, TFC, micronized small intestinal submucosa tissue (SIS), or TFC absorbed to SIS. Blood flow in both limbs was assessed with laser Doppler perfusion imaging. Tissues harvested at Day 48 were assessed immunohistochemically for vessel density; in situ hybridization and quantitative real-time PCR were employed to determine miR-126 expression. RESULTS LDP ratios were significantly elevated, compared to placebo control, on day 28 in all treatment groups (p=0.0816, p=0.0543, p=0.0639, for groups 2-4, respectively) and on day 36 in the TFC group (p=0.0866). This effect correlated with capillary density in the SIS and TFC+SIS groups (p=0.0093 and p=0.0054, respectively, compared to placebo). A correlation was observed between miR-126 levels and LDP levels at 48 days in SIS and TFC+SIS groups. CONCLUSIONS A single bolus administration of TFC and SIS had early, transient effects on reperfusion and promotion of ischemia repair. The effects were not additive. We also discovered that TFC modulated miR-126 levels that were expressed in cell types other than endothelial cells. These data suggested that TFC, alone or in combination with SIS, may be a potent therapy for patients with CLI that are at risk of amputation.
Keywords: transplantace kmenových buněk; Perfusion; Intestine, Small; mikro RNA; reperfuzní poškození; Gene Expression Regulation; Disease Models, Animal; Middle Aged; Ischemia; tenké střevo; Reperfusion Injury; perfuze; Cell-Derived Microparticles; Intestinal Mucosa; MicroRNAs; Extracellular Matrix; ischemie; Laser-Doppler Flowmetry; regulace genové exprese; modely nemocí na zvířatech; ženské pohlaví; zvířata; Humans; králíci; laser doppler flowmetrie; Stem Cell Transplantation; Skin; Rabbits; Extremities; lidé středního věku; střevní sliznice; Adipose Tissue; mikropartikule; Stem Cells; kmenové buňky; Female; končetiny; tuková tkáň; extracelulární matrix; kůže; lidé; Animals